SOUTH KOREAN POLICY TOWARDS ASEAN (Journal of Oriental Studies, 2023)
ASEAN has been the fourth trading partner of South Korea for a long time, so Seoul has been pursuing an active foreign policy towards the regional bloc of Southeast Asian countries. Conventionally, South Korean scientists divide the ASEAN countries into four levels of development: 1) countries with high incomes - Singapore, Brunei; 2) countries with incomes above the middle - Malaysia; and 3) Middle incomes - Thailand, Indonesia and the Philippines; 4) and low incomes - Cambodia, Laos, Myanmar and Vietnam. South Korea has developed its own approach to each of these countries. The main competitors in relation to the ASEAN countries are China and Japan, which produce products similar to South Korean ones. In order to create favorable conditions for itself in trade and compete with other regional players, South Korea has concluded a Free Trade Agreement with the ASEAN countries. The main problems for doing business are different legislation, problems with respect for intellectual property rights. In addition, the mutual opening of the markets of ASEAN and South Korea poses a threat to South Korean farmers, since agricultural products in most ASEAN countries are cheaper, which can lead to the ruin of South Korean farmers.In order to penetrate the markets of the ASEAN countries, South Korea actively uses "soft power" consisting of culture, education and medicine. South Korea also provides ASEAN developing countries with Official Development Assistance, especially those rich in natural resources.Key words: Republic of Korea, international organizations, ASEAN, Southeast Asia.